2003
DOI: 10.1046/j.1523-1739.2003.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasiveness of Some Biological Control Insects and Adequacy of Their Ecological Risk Assessment and Regulation

Abstract: The problem of invasive species has reignited interest in biological control as a management tool. Classical biological control involves deliberate release of exotic natural enemies into new environments in an attempt to limit the density of an invasive species. Persistent, sustained limitation of invasive species by coevolved natural enemies is a seductive concept. Evidence now suggests, however, that biological control through the release of natural enemies can carry unanticipated ecological risks. There hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(79 citation statements)
references
References 65 publications
(121 reference statements)
1
74
0
4
Order By: Relevance
“…A mechanistic understanding of invasive species effects on native species is essential to predicting their impacts if they invade new communities (Louda et al 2003a(Louda et al ,b, 2005. Holt and Hochberg (2001) suggested that exotic biological control insects that attack native plants and do not strongly suppress the targeted weed can mediate indirect effects of invasive weeds on acquired native hosts, as shown in this study.…”
Section: Indirect Effects Imposed By Invasive Speciesmentioning
confidence: 99%
“…A mechanistic understanding of invasive species effects on native species is essential to predicting their impacts if they invade new communities (Louda et al 2003a(Louda et al ,b, 2005. Holt and Hochberg (2001) suggested that exotic biological control insects that attack native plants and do not strongly suppress the targeted weed can mediate indirect effects of invasive weeds on acquired native hosts, as shown in this study.…”
Section: Indirect Effects Imposed By Invasive Speciesmentioning
confidence: 99%
“…In these prairies, R. conicus oviposits not only on wavyleaf thistle, but it also has heavily impacted a second, native thistle, Platte thistle (C. canescens Nutt.) Louda and Arnett 2000;Louda et al 2003;Rose et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, the release of exotic insects entails a risk to native plants and communities (Howarth, 1991;Simberloff and Stiling, 1996;Louda et al, 1997Louda et al, , 1998Stiling and Simberloff, 1999). Prediction of both the risk and the ecological impact of exotic insects poses a critical challenge (Louda, 1999a;Strong and Pemberton, 2000;Louda et al, 2003aLouda et al, , 2003b.…”
Section: Introductionmentioning
confidence: 99%